PENERAPAN METODE DISKUSI UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VA SD NEGERI 004 TEMBILAHAN KECAMTAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Rosmida Rosmida (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
The background of this study is the lack of IPS students' learning outcomes, from 22 students only 36.36% or 8 students who managed to achieve a minimum completeness criteria (KKM) established school with a class average value of 61.75. Based on this the researchers conducted a classroom action research with the aim to improve learning outcomes IPS students through the application of methods of discussion. This research is a class act, who performed a total of two cycles consisting of two meetings, the data of this study focuses on the data increase learning outcomes and increase student mastery learning outcomes IPS. The study states that the results of social studies students has increased in each cycle, the initial data is the number of students who completed 8 students (36.36%) with an average of learning outcomes at 61.75. In the first cycle has increased the number of students who completed up to 16 students (72.73%) with an average of learning outcomes at 73.90, and the second cycle the number of students who pass the increase to 22 students (100.00%) with a mean -rata learning outcomes at 87.75. Based on these results it can be concluded that the application of the method of discussion to improve learning outcomes IPS students of class V A SD Negeri 004 Tembilahan Kecamatan Tembilahan.